Potensi Ekstrak Metanol Daun Magnolia sumatrana var. glauca (Blume) Figlar & Noot Sebagai Bioinsektisida Terhadap Hama Sitophilus oryzae Pada Benih Padi - Syahputri, Aulia; Fitriani, Fitriani; Putri, Kartika A. (Jurnal Biologi Papua, 2024)
The decrease in seed quality is caused by the pest Sitophilus oryzae which attacks rice seeds. Efforts to improve seed quality by using methanol extract of Magnolia sumatrana leaves which contain secondary metabolite compounds which have potential as bioinsecticides. This research was to find out whether there is a bioinsecticide effect from the methanol extract of M. sumatrana leaves and what concentration of bioinsecticide from the methanol extract of M. sumatrana leaves is effective. This research used a Completely Randomized Design (CRD) with 8 treatments and 5 replications. Data analysis used ANOVA at a significance level of 5% and continued with the Least Significant Difference Test (LSD). Based on the research results, there was an effect of using M. sumatrana leaf methanol extract on S. oryzae pest mortality, seed toxicity, and seed viability after treatment. Application of M. sumatrana leaf methanol extract at a concentration of 5% effectively increased S. oryzae pest mortality by 93.20%, seed toxicity by 0.03 g, and seed viability by 92.62% after treatment.  .